Physical Activity in University Students: A Comparative Analysis of Motivations in Ecuador and Spain; Atividade física em estudantes universitários: uma análise comparativa das motivações no Equador e na Espanha; Actividad física en estudiantes universitarios: un análisis comparativo de motivaciones en Ecuador y España - Farias-Valenzuela, C (Universidad Nacional, 2025)
Purpose: The aim of the present study was to determine the relationship between the motives for physical activity according to the sex of Ecuadorian and Spanish university students and to analyze the existing differences according to sex and country. Methodology: The sample consisted of 1776 students from different public university centers in Ecuador (513 men and 899 women with a mean age of 21.2 ± 3.5 years) and Spain (122 men and 242 women with a mean age of 21.8 ± 2.6 years). An ad hoc sociodemographic questionnaire and the Goal Content for Exercise Questionnaire were used for data collection. The analysis was performed using Spearman’s correlation coefficient and the Mann–Whitney U test. Results: The results show that in Ecuadorian students, all motives correlate positively with each other, whereas in Spanish students, the only motives that do not correlate are social affiliation with image and health improvement with social recognition. In terms of sex, there were significant differences in social affiliation, social recognition, and skill development in both countries as well as in health improvement in Ecuadorian students with higher mean values for men. With respect to country, there are significant differences in health improvement and skill development in Spanish students and in the motive of social recognition in Ecuadorian students. Conclusions: Finally, the main motivations for physical activity in both countries were health improvement and skill development in men and women. © 2025 Universidad Nacional. All rights reserved.